The project method in the process of the development of infographic competence of future bachelors of cyber security - Matviichuk-Yudina, O.; Loboda, S. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the specifics of using the projects method in the process of forming infographic competence of undergraduates studying for a Bachelor's degree in "Cyber Security" (specialty 125) during the laboratory classes on the subject "Computer Graphics". The paper considers theoretical bases of using the project method in the process of forming infographic competence of future bachelors of cyber security, which are grounded on the principle of close interconnection of science and practice. The article analyzes foreign experience in the formation and definition of professional competences presented in the "Industrial Model of Cyber Security" which is applied in the process of professional training in higher educational institutions of the USA and many other countries of the world. Methodological recommendations for the use of the project method in laboratory classes dedicated to the topic "Infographics" for future bachelors of cyber security are presented in the work. As an example, the authors suggest considering the project of an infographic object created on the basis of the software application Photoshop, which graphically represents the main provisions of the Law of Ukraine «On Basic Principles of Ukraine's Cyber Security».